Hubungan Pola Makan Terhadap Kejadian Anemia Pada Remaja Di SMAN 1 Godean - Desi Agrevina; Evi Wahyuntari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Eating patterns refer to the way individuals maintain health, nutrition status, prevent, and help cure diseases by managing the quantity and types of food consumed. According to the 2018 Basic Health Research (Riskesdas), anemia in Indonesia is estimated to affect 23.7% of the population.  Among adolescents aged 15-24 years, approximately 32% are affected, with a higher prevalence among females (27.2%) compared to males (20.3%), a difference of 6.9%. Objective: The aim of this study is to determine the correlation between eating patterns and the incidence of anemia among adolescents at SMAN (State Senior High School) 1 Godean. Method: This research employed a cross-sectional approach, with simple random sampling for data collection. Bivariate analysis was performed to determine the correlation between the independent and dependent variables. The analysis was conducted using non-parametric statistical tests, specifically the Chi-square test. Result: The results of the Chi-square test indicated a significant correlation between eating patterns and the incidence of anemia in adolescents at SMAN 1 Godean, with a p- value of 0.010 (p < 0.05). Conclusion: The study concludes that there is a correlation between eating patterns and the occurrence of anemia among female adolescents at SMAN 1 Godean. Recommendation: It is recommended that female adolescents, particularly the respondents, consume balanced foods containing carbohydrates, proteins, fats, fiber, and iron-rich foods.